ChemInform Abstract: Na3SbS3: Single Crystal X‐Ray Diffraction, Raman Spectroscopy, and Impedance Measurements. Issue 18 (11th April 2013) - Pompe, Constantin; Pfitzner, Arno
Abstract Pale yellow and air and moisture sensitive Na3SbS3 is prepared by reaction of stoichiometric mixtures of Na2S, Sb, and S (graphite‐coated silica tube, 1.